Nitrogen immobilization in plant growth substrates: clean chip residual, pine bark, and peatmoss - Boyer, Cheryl R.; Torbert, H. Allen; Gilliam, Charles H.; Fain, Glenn B.; Gallagher, Thomas V.; Sibley, Jeff L. (My University, 2013)
Rising costs of potting substrates have caused horticultural growers to search for alternative, lower-costmaterials. Objectives of this study were to determine the extent of nitrogen immobilization and microbial respiration in a high wood-fiber content substrate, clean chip residual. Microbial activity and nitrogen availability of two screen sizes (0.95 cm and 0.48 cm) of clean chip residual were compared to control treatments of pine bark and peatmoss in a 60-day incubation experiment. Four rates (0, 1, 2, or 3mg) of supplemental nitrogen were assessed. Peatmoss displayed little microbial respiration over the course of the study, regardless of nitrogen rate; followed by pine bark, 0.95 cm clean chip residual, and 0.48 cm clean chip residual. Respiration increased with increasing nitrogen. Total inorganic nitrogen (plant available nitrogen) was greatest with peatmoss; inorganic nitrogen in other treatments were similar at the 0, 1, and 2mg supplemental nitrogen rates, while an increase occurred with the highest rate (3 mg). Clean chip residual and pine bark were similar in available nitrogen compared to peatmoss. This study suggests that nitrogen immobilization in substrates composed of clean chip residual is similar to pine bark and can be treated with similar fertilizer amendments during nursery production.
Keywords: Potting substrates; Nitrogen immobilization; Microbial respiration